Enhancing Food Poisoning Emergency Response Skills Through Simulation-Based Training Among Special Education Teachers: A Pre-Experimental Study - Deri Raihan Aljabar; Gatot Suparmanto; Aisyah Nur Azizah (Genius Journal of Nursing, 2026)
Background: Food poisoning outbreaks in schools remain an important public health concern because teachers often become the first responders during emergencies. However, competencies related to post–food poisoning management remain limited, particularly in special education settings. Objectives: To examine the effect of simulation-based post–food poisoning management training on teachers’ skills at SLB Negeri 1 Bantul. Methods: A quantitative pre-experimental study using a one-group pretest–posttest design was conducted among 51 teachers selected through simple random sampling. Participants received structured simulation training focused on post–food poisoning stabilization procedures. Teachers’ skills were assessed using an observational checklist before and after the intervention. Data were analyzed using the Wilcoxon Signed Rank Test. Results: Before training, most participants demonstrated poor (58.8%) and fair (27.5%) skill levels. Following simulation, all participants achieved very good skill levels (100%). Statistical analysis demonstrated significant improvement after the intervention (Z = –6.224; p < 0.001), with all participants showing positive rank changes. Conclusions: Simulation-based training effectively improved teachers’ post–food poisoning management skills and may strengthen emergency preparedness in school settings through improved early stabilization capacity.